PERBEDAAN KETRAMPILAN MAHASISWA DALAM MEMASANG INFUS DENGAN MENGGUNAKAN METODE PEMBELAJARAN DEMONSTRASI DAN MEDIA AUDIO VISUAL DI AKADEMI KEPERAWATAN YAKPERMAS BANYUMAS - Setyo Upoyo, Arif; Astuti, Dwi; Purbo Juwono, Wahyu (LPPM STIKES MUHAMMADIYAH GOMBONG, 2013)
Students as learner must be active looking for knowledge that needed from any resources. Lecture is not primary knowledge resources. In Student Centered Learning, lecture have role as learning facilitator. Learning in laboratory for skill practice with demonstration method need more time and lecture. The objective is to know the difference student’s skill in infuse administration with use demonstration method learning and audiovisual aid. Research design used quasi experiment. Subject research divided two groups. One group used demonstration method learning and the other used audiovisual aid, than skill infuse administration was evaluated. The population is student Yakpermas Nursing Academy in second semester. Sampling technical used simple random sampling. Analysis used Mann Whitney U test. The result : student skill in infuse administration used demonstration method are 25% poor, 50% good, 25% very good, student skill used audiovisual aid are 34,78% poor, 43,48% good, 21,74% very good and p value of two methods difference is 0,423. Conclusion: there is no significant different student’s skill infuse administration use demonstration method learning and use audiovisual aid. Key word : demonstration methode learning, audiovisual aid, student’s skill, infuse administration.